Inhibition of lipopolysaccharide (LPS)-induced neuroinflammatory response by polysaccharide fractions of Khaya grandifoliola (C.D.C.) stem bark, Cryptolepis sanguinolenta (Lindl.) Schltr and Cymbopogon citratus Stapf leaves in raw 264.7 macrophages and U87 glioblastoma cells - Francine Kengne Mediesse; Thaddée Boudjeko; Anantharaju Hasitha; Matharasala Gangadhar; Wilfred Fon Mbacham; Perumal Yogeeswari (BMC, 2018)
Abstract Background Khaya grandifoliola (C.D.C.) stem bark, Cymbopogon citratus (Stapf) and Cryptolepis sanguinolenta (Lindl.) Schltr leaves are used in Cameroonian traditional medicine for the treatment of inflammatory diseases. Several studies have been performed on the biological activities of secondary metabolites extracted from these plants. However, to the best of our knowledge, the anti-neuro inflammatory and protective roles of the polysaccharides of these three plants have not yet been elucidated. This study aimed at investigating potential use of K. grandifoliola, C. sanguinolenta and C. citratus polysaccharides in the prevention of chronic inflammation. Methods Firstly, the composition of polysaccharide fractions isolated from K. grandifoliola stem bark (KGF), C. sanguinolenta (CSF) and C. citratus (CCF) leaves was assessed. Secondly, the cytotoxicity was evaluated on Raw 264.7 macrophages and U87-MG glioblastoma cell lines by the MTT assay. This was followed by the in vitro evaluation of the ability of KGF, CSF and CCF to inhibit lipopolysaccharides (LPS) induced overproduction of various pro-inflammatory mediators (NO, ROS and IL1β, TNFα, IL6, NF-kB cytokines). This was done in Raw 264.7 and U87-MG cells. Finally, the in vitro protective effect of KGF, CSF and CCF against LPS-induced toxicity in the U87-MG cells was evaluated. Results CCF was shown to mostly contain sugar and no polyphenol while KGP and CSP contained very few amounts of these metabolites (≤ 2%). The three polysaccharide fractions were non-toxic up to 100 μg.mL− 1. All the polysaccharides at 10 μg/mL inhibited NO production, but only KGF and CCF at 12.5 μg/mL down-regulated LPS-induced ROS overproduction. Finally, 100 μg/mL LPS reduced 50% of U87 cell viability, and pre-treatment with the three polysaccharides significantly increased the proliferation. Conclusion These results suggest that the polysaccharides of K. grandifoliola, C. citratus and C. sanguinolenta could be beneficial in preventing/treating neurodegenerative diseases in which neuroinflammation is part of the pathophysiology.